2016
DOI: 10.3727/096504016x14611963142254
|View full text |Cite
|
Sign up to set email alerts
|

miR-34b Targets HSF1 to Suppress Cell Survival in Acute Myeloid Leukemia

Abstract: Acute myeloid leukemia (AML) is the most lethal hematological malignancy, and the occurrence of chemoresistance prevents the achievement of complete remission following the standard therapy. MicroRNAs have been extensively investigated as critical regulators of hematopoiesis and leukemogenesis, and they represent a promising strategy for AML therapy. In this study, we identified miR-34b as a novel regulator in myeloid proliferation and apoptosis of leukemic cells. We found that miR-34b was developmentally upre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
(17 reference statements)
2
15
0
Order By: Relevance
“…Many researchers have investigated the role of miR-34 family in leukemia, especially miR-34a. For instance, Li et al reported that miR-34b was significantly lower expressed in AML blood samples and AML cell lines, and miR-34b inhibited cell viability and promoted cell apoptosis in AML cells by targeting HSF1 [27]. Yang et al showed that miR-34c was lower expressed and served as a biomarker in predicting prognosis in patients with AML [28].…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have investigated the role of miR-34 family in leukemia, especially miR-34a. For instance, Li et al reported that miR-34b was significantly lower expressed in AML blood samples and AML cell lines, and miR-34b inhibited cell viability and promoted cell apoptosis in AML cells by targeting HSF1 [27]. Yang et al showed that miR-34c was lower expressed and served as a biomarker in predicting prognosis in patients with AML [28].…”
Section: Discussionmentioning
confidence: 99%
“…ASS1 (Argininosuccinate synthetase 1) gene product is responsible for the process of arginine biosynthesis; however, Miraki-Moud et al (34), reported that most AML lacked ASS1 expression, which may be due to small sample size and the different detection methods. Other genes, such as HSF1 (Heat-shock transcription factor 1), WT1 (Wilms tumor 1), ACTA2 (Actin, alpha 2), SLC15A2 (Solute carrier family 15 member 2), PDLIM1 (C terminal LIM domain protein 1), and CTSA (Cathepsin A) were revealed by our meta-analysis, and even some of them have been reported previously with increased expression in AML and MDS (35,36), their potential as diagnostic or prognostic markers in MDS and AML needs further exploration. Among the top ten downregulated DEGs, although MME encoded protein MMP12 was believed to be related with acute lymphocytic leukemia (ALL) diagnosis (37), its role in MDS and AML remains to be demonstrated.…”
Section: Discussionsupporting
confidence: 50%
“…In addition, HSF1 regulates HSPs to maintain the protein balance, thereby inhibiting apoptosis of multiple myeloma cells [22]. HSF1 also regulates the classical Wnt-β-catenin signaling pathway in the inhibition of acute lymphoma cell apoptosis [23]. In the present study, protein chip analysis revealed that SMAC-mediated mitochondrial apoptosis-related proteins were the most significantly enriched in pancreatic cancer cell apoptosis.…”
Section: Discussionmentioning
confidence: 64%